The Life and Death of States : Central Europe and the Transformation of Modern Sovereignty - Wheatley, Natasha (Book collections on Project MUSE., 2023)
"Canonical theorists of sovereignty (Hobbes, Rousseau, and others) put the monopoly of power at the center of their definitions. These thinkers abstracted from western European experiences to universal norms. In the wake of their transformative contributions, states that did not fit the model appeared to be underdeveloped or deviant. Labels such as "provisional" or "irregular" rendered them irrelevant to theorizing and, worse, political problems that needed to be solved. One early "anomaly," says historian Natasha Wheatley, was the Habsburg Empire. Layered as it was with imperial, national, and regional sovereignty, its trajectory was not one of progress toward a unitary state. Instead, it encompassed compound polities, or states bundled together under experimental constitutional orders. Wheatley's aim in this book is to theorize from Central Europe to see how sovereignty can be produced in a complex world. In reconstructing this political and legal history, Wheatley treats Austria-Hungary as a crucible for modern legal theory. The serial remaking and eventual unmaking of imperial sovereigny in Central Europe showed how old-world dynastic conceptions of sovereignty were translated into abstract categories of modern legal thought. In so doing, she uncovers the irresolvable tensions and strategic silences in modern political theory: the presumed unity and timelessness of states. Eschewing explanations of "failure," she instead uncovers how the Central European experience crystallized legal questions that would arise again in the era of global decolonization, connecting the story of the end of empire to the birth of new nations throughout the twentieth century. In this respect, the work serves not only as a history of Central Europe but also a "prehistory" of the era of decolonization"--